2005
DOI: 10.1111/j.1439-0523.2005.01125.x
|View full text |Cite
|
Sign up to set email alerts
|

Collection and evaluation of grasspea (Lathyrus sativus L.) germplasm of central Italy

Abstract: Characterization of 16 grasspea (Lathyrus sativus L.) accessions collected in central Italy (Marche region) was performed for morphological and agronomic traits and for 3-(-N-oxalyl)-L-2,3 diaminopropionic acid (ODAP) content. Field trials, carried out in two locations, revealed high among-population genetic variation. In particular, an evident differentiation between commercial populations, cultivated by market-oriented farms, and household populations (not marketoriented) was found. Genotype · environment in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 12 publications
1
18
0
Order By: Relevance
“…Levels below 2 g kg −1 are generally considered safe for humans. The ODAP levels recorded in this study (Table 4) were comparable to those reported in the literature for other Italian local populations,21, 22, 37 but they were higher than the mean value reported by Grela et al 23 for grass pea accessions cultivated in the Mediterranean basin (0.847 g kg −1 ) and lower than those detected in exotic accessions 15, 28, 29, 36, 37. The ecotypes Calitri, Carife, Marchigiano, Monti Frentani and Pietranera, characterised by especially high ODAP levels at Guardia Perticara in the first growing season, were excluded from the subsequent field trials.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Levels below 2 g kg −1 are generally considered safe for humans. The ODAP levels recorded in this study (Table 4) were comparable to those reported in the literature for other Italian local populations,21, 22, 37 but they were higher than the mean value reported by Grela et al 23 for grass pea accessions cultivated in the Mediterranean basin (0.847 g kg −1 ) and lower than those detected in exotic accessions 15, 28, 29, 36, 37. The ecotypes Calitri, Carife, Marchigiano, Monti Frentani and Pietranera, characterised by especially high ODAP levels at Guardia Perticara in the first growing season, were excluded from the subsequent field trials.…”
Section: Resultssupporting
confidence: 86%
“…With these concepts in mind, some studies aimed at investigating the genetic variation present within the Italian germplasm have started recently. Tavoletti and co‐workers19–21 evaluated the differentiation of morphological, agronomic and genetic traits detectable in local populations from central Italy. Granati et al 22 and Grela et al 23 compared the seed composition of some Italian populations with that of exotic accessions.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the focus was on populations of a relatively restricted area. Genetic variation for agronomic and quality traits had already been detected among these populations in previous field investigations (Tavoletti and Capitani 2000, Tavoletti et al. 2005).…”
Section: Discussionmentioning
confidence: 56%
“…2003). In particular, a grasspea collection including accessions collected mainly in the Marche region has been assembled (Tavoletti et al. 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation